Infección por virus respiratorios en adultos hospitalizados en un Servicio de Medicina Interna - Riquelme, Raúl; Rioseco, María Luisa; Agüero, Yasna; Ubilla, Daniela; Mechsner, Pamela; Inzunza, Carlos; Riquelme, Maurico (Revista Médica de Chile, 2014)
Background: Respiratory viral infections (RVi) can be associated with a wide range of clinical manifestations. Aim: to investigate the frequency and clinical manifestations of RVi among adult patients during winter hospitalizations. Patients and methods: All patients admitted to the hospital with flu like disease and those with fever or exacerbation of any underlying disease during hospitalization without an evident cause, were prospectively enrolled. A direct immunofluorescence (DIF) of nasopharyngeal aspirate for influenza A (IA) and B, parainfluenza 1, 2 and 3, adenovirus, respiratory syncytial virus (RSV) and metapneumovirus, was performed. Epidemiological and clinical data were recorded. Results: Between May and September 2012, 975 adults were admitted to the Internal Medicine Unit of Puerto Montt Hospital and in 128 (13%) patients, DIF was carried out. DIF was positive in 44 patients (34%) aged 65 ± 20 years, 68.2% females, corresponding to 4.5% of total hospitalizations. Eighty six percent of the latter had at least one co-morbidity, mainly asthma and chronic respiratory diseases in 34.1%, diabetes in 29.5%, cardiac problems in 25% and congestive heart failure in 20.5%. The most common RVi were RSV (n=21, 48%) and IA (n=17, 39%). Six patients had a nosocomial RVi. Patients infected with IA had a significantly higher frequency of fever and bronchial hyper reactivity than those infected with RSV. RVi were associated with exacerbation of underlying disease in 62% of cases and pneumonia in 27%. Two patients had a viral pericarditis. Conclusions: RVi are an important cause of adult morbidity and their detection should be routine in adult patients hospitalized during winter.